Simulasi tegangan pada pengaruh putaran roda terhadap speed bump menggunakan metode FEM - Hidayat, R.; Haryono, M.B. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2018)
The interaction between tires with road surface is very important because it can reduce the risk of accidents due to damage to the tire. This research was investigated the stress distribution as a result on pressure of tires rolling across speed bump. The research methode used solid work and abaqus application to simulation, the paramaters on research used variation on high speed bump (75mm, 120mm and 160mm) and tires speed (8, 20 and 30kmh). The result showed the higher load recived by tires, the higher stress produced The interaction between tires with road surface is very important because it can reduce the risk of accidents due to damage to the tire. This research was investigated the stress distribution as a result on pressure of tires rolling across speed bump. The research methode used solid work and abaqus application to simulation, the paramaters on research used variation on high speed bump (75mm, 120mm and 160mm) and tires speed (8, 20 and 30kmh). The result showed the higher load recived by tires, the higher stress produced